Evaluasi Kebijakan Pertahanan Negara Indonesia dalam Membangun Efektifitas Strategi Penangkalan Wilayah. - Sarjito, Aris (Journal of Political Issues, 2025)
This research delves into the analysis of Indonesia's national defense policy and its influence on the development of area denial strategies, with a focus on maritime security. The background highlights the importance of understanding the evolution of Indonesia's defense policy and its implications for regional security dynamics. The aim is to examine the alignment between Indonesia's defense policy objectives and the formulation of area denial strategies, utilizing qualitative research methods with secondary data. Using Creswell's guidelines for qualitative research design, this study carefully looks at existing literature, policy documents, and historical records to look into three main areas: how Indonesia's national defense policy has changed over time, what its main area denial strategies are, and how defense policy has affected the creation of these strategies. Findings reveal a shift in Indonesia's defense posture towards a more maritime-centric approach, with investments in maritime defense systems, A2/AD measures, and asymmetric tactics. Moreover, the analysis demonstrates a significant alignment between Indonesia's defense policy objectives and the development of area denial strategies, highlighting the country's commitment to safeguarding its territorial sovereignty and maritime interests. The conclusion underscores the importance of a holistic understanding of Indonesia's defense policy for enhancing regional security and stability.